Identification of Potential Antimalarial Compound(s) from Alkaloid, Flavonoids and Phenolics Rich Extracts of Piliostigma reticulatum Leaf - Abdulhafiz Lamiya; Adamu Jibril Alhassan; Maryam Abdulkadir Dangambo; Hauwa Ahmed Zailani (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
Malaria is a deadly vector born disease caused by Plasmodium spp with increasing morbidity and mortality in sub-Saharan Africa. Ethnobotanical studies and phytochemical screening remains the mainstay in the hunt of bioactive secondary metabolites from natural sources needed to confront the growing challenges faced by available drugs used in the treatment of many infectious diseases malaria inclusive. This study aimed at identifying potential antimalarial compound(s) in some Piliostigma reticulatum extracts. In vivo technique was used to assay for antimalarial activities of P. reticulatum extracts and spectroscopic technique was used to characterize compounds present in the extract. Top hit compound against some Plasmodium spp targets were identified using in silico technique. In vivo study revealed phenolic rich extract to exhibit significant antimalarial activity (P<0.05) compared to other extracts and twenty five compounds were identified in the extract spectroscopically. Molecular docking of the compounds against some Plasmodium falciparum targets (PMII, HAP, FP-2 and PfENR) revealed ethylene brassylate as the top hit compound that inhibited PMII, FP-2 and PfENR with binding affinity of -7.3, -7 and -6.5Kcal/mol respectively, whereas 2-hexadecanol was the top hit for HAP with binding affinity of -6.4Kcal/mol. In silico ADMET analysis of the top hits revealed that they both possess drug-like property, metabolizable and relatively safe. This finding gives credence to the use of the plant in malaria treatment and identified two compounds Ethylene brassylate and 2-hexadecanol as promising antimalarial drug candidates which can be harnessed for discovery of novel antimalarial drug.